Safety and Efficacy of Antihypertensive Prescription at Emergency Department Discharge. (22nd April 2015) - Brody, Aaron; Rahman, Tahsin; Reed, Brian; Millis, Scott; Ference, Brian; Flack, John M.; Levy, Phillip D.; Sinert, Richard
Abstract Background Poor blood pressure (BP) control is a primary risk factor for target organ damage in the heart, brain, and kidney. Uncontrolled hypertension is common among emergency department (ED) patients, particularly in underresourced settings, but it is unclear what role ED providers should play in the management of chronic antihypertensive therapy. Objectives The objective was to evaluate the safety and efficacy of prescribing antihypertensive therapy from the ED. Methods This was a retrospective study of data pooled from two prospective, longitudinal, randomized controlled trials, both of which enrolled ED patients with asymptomatic hypertension. Antihypertensives were prescribed at emergency physician discretion, and this was not related to randomization arm. Demographic data, BP at screening and randomization visit, and data on adverse effects potentially related to antihypertensive therapy were compiled. Means were compared using Student's t‐tests, and proportions were compared using chi‐square tests. The effect of antihypertensive therapy on BP control was further analyzed using multivariable regression modeling controlling for age, race, sex, hypertension history, study cohort, and ED BP. Results Data were abstracted for 217 subjects. The median interval from ED visit to randomization was 12 days. Seventy‐six subjects (35%) received one or more prescriptions for antihypertensive therapy. Age, sex, race, hypertension history, and mean duration of hypertension were equivalent between groups. Although mean ED BP was higher among those who received prescriptions, the mean systolic BP (sBP) reduction from ED to randomization was significantly greater (difference = 19 mm Hg, 95% confidence interval = 12 to 26 mm Hg). No patient in either group had an sBP less than 100 mm Hg at randomization. On multiple regression modeling, randomization sBP reduction was independently associated with antihypertensive prescription (p = 0.001). The incidence of adverse effects was equivalent and low in both groups. No new neurological deficits, ischemic events, or life‐threatening anaphylactic reactions were reported in either group. Conclusions Prescription of antihypertensive medication from the ED is associated with significantly lower sBP at short‐term outpatient follow‐up. Antihypertensive therapy was not associated with an increased incidence of adverse events, and BP reduction did not exceed potentially harmful levels. Initiation of chronic antihypertensive therapy in the ED is safe and effective and may be a reasonable consideration for at‐risk populations.